Pro- and anti-inflammatory cytokines in cutaneous leishmaniasis: a review. (17th August 2016) - Maspi, Nahid; Abdoli, Amir; Ghaffarifar, Fathemeh
Abstract : Cutaneous leishmaniasis (CL) is caused by different species of the genus Leishmania . Pro- and anti-inflammatory cytokines play different roles in resistance/susceptibility and the immunopathogenesis of Leishmania infection. The balance and dynamic changes in cytokines may control or predict clinical outcome. T helper 1 (Th1) inflammatory cytokines (especially interferon-γ, tumor necrosis factor-α and interleukin-12) are the crucial factors in the initiation of protective immunity against L. major infection, whereas T helper 2 cytokines including IL-5, IL-4, and IL-13 facilitate the persistence of parasites by downregulating the Th1 immune response. On the other hand, aggravation of inflammatory reactions leads to collateral tissue damage and formation of ulcer. For this reason, immunity system such as T regulatory cells produce regulatory cytokines such as transforming growth factor-β and IL-10 to inhibit possible injures caused by increased inflammatory responses in infection site. In this article, we review the role of pro- and anti-inflammatory cytokines in the immunoprotection and immunopathology of CL.